Thermal performance analysis of a porous solar cavity receiver. (August 2020) - Chen, Sheng; Li, Wenhao; Yan, Fuwu
Abstract: A solar cavity receiver filled with a porous layer now is popularly found in solar energy industry. As its thermal performance will influence the efficiency of solar energy utilization systems considerably, deep understanding on it is urgent for the development of solar energy industry. In the present work, the influences of thickness, effective thermal conductivity and permeability of a porous layer on thermal performance of a porous solar cavity receiver are investigated comprehensively for the first time. The analysis is carried out not only from the viewpoint of the first law of thermodynamics but also from the second law of thermodynamics. Three new findings are obtained: (1) a critical value of thickness of the porous layer, (2) a critical value of effective thermal conductivity of the porous layer and (3) a critical value of permeability of the porous layer, across which the thermal performance of the solar receiver will alter significantly. In addition, some comparison is conducted between the observations in this research and those in previous publications to check the effects of the configuration and flow driven mechanism of a porous solar cavity receiver on its thermal performance for the first time. Highlights: Some critical effects are investigated. Three critical values are observed. Comparison with available literature is conducted. Useful guides for practical design.